ГИПЕРБОЛАЛЫҚ ФУНКЦИЯЛАР ҲӘМ ОЛАР АРАСЫНДАҒЫ ҚАТНАСЛАР - Калекеева, Т.Т. (FAN va JAMIYAT, 2024)
The article discusses hyperbolic functions, the derivative of hyperbolic functions, the ratio and some properties of hyperbolic functions.